Effect of Implementation of COVID-19 Guidelines on the Lives of Haemophilia Patients Registered with the Haemophilia Treatment Centre, Rawalpindi - Tahira Zafar , Humera Siddique , Raana Zeeshan ,Lubna Zafar, (Journal of Rawalpindi Medical College, 2021)
Introduction: The development of isolation strategies to prevent spread of COVID -19 could affect the lives of Haemophilia patients beyond the risk of infection. In order to prevent this, the Haemophilia Treatment Centre, Rawalpindi, adopted additional combat strategies including the use of telephonic and video consultations, dispensing medicine at home and single day treatments. Objective: To assess the impact of COVID -19 pandemic and associated lockdown and changes in Standard Operating Procedures (SOPs) on the working of Haemophilia Treatment Centre, Rawalpindi and on the lives of its registered patients. Methods: An observational study was carried out at the Haemophilia Treatment Centre, Rawalpindi, between September, 2019 and August, 2020. Written records of frequency of virtual/physical visits to the Centre, treatment compliance, bleeding episodes, musculoskeletal health, psychosocial health, pain, disability and inhibitor status were obtained from six months pre pandemic and followed prospectively six months into the pandemic. Results: The Haemophilia Treatment remained open and functional throughout the study period. All staff members followed specially developed Haemophilia Treatment Centre guidelines vigilantly. Since telemedicine was encouraged , a rise in telephonic consultations was observed and therefore, no difference in overall visits was observed among the Pre- and Intra- Pandemic eras. The option of at-home dispensing of medicine via courier was available, and therefore, all patients remained treatment compliant. Among patients on Low Dose Prophylaxis (LDP) regimen, no difference in musculoskeletal health, bleeding episodes, inhibitor status, psychosocial health and nutritional status was observed among the two time periods. None of the staff members or patients were affected by the Covid-19. Conclusion: Our study shows that timely anticipation of potential impact of a pandemic and prompt development of modified mechanisms can indeed make the working of a Health Care Centre successful and prevent side effects on the lives of its patients.